1997
DOI: 10.1046/j.1365-2311.1997.00083.x
|View full text |Cite
|
Sign up to set email alerts
|

Preference for protected feeding sites by larvae of the willow‐feeding leaf beetle Galerucella lineola

Abstract: 1. Free‐living insects are often thought of as more vulnerable to environmental hazards than concealed insects, such as galling or mining insects. The possibility that larvae of the free‐living leaf beetle Galerucella lineola seek out existing plant structures and thereby become partly concealed was explored. 2. Neonate larvae of G. lineola frequently feed in rolled‐in margins of young leaves of their host plant, Salix viminalis. In addition to nutritional benefits from feeding on young leaves, larvae may also… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
71
0
1

Year Published

2001
2001
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(74 citation statements)
references
References 18 publications
2
71
0
1
Order By: Relevance
“…A similar behavior was observed in neonate larvae of Galeruca lineóla (Galerucinae), which tend to move upward searching for physical shelter in young rolled leaves of its host plant (Larsson et al 1997). This behavior may also be due to nutritional demands, since young leaves are tender and usually contain more nutrients and water than mature leaves (Coley 1983;Ohmart et al 1985).…”
Section: Discussionsupporting
confidence: 52%
“…A similar behavior was observed in neonate larvae of Galeruca lineóla (Galerucinae), which tend to move upward searching for physical shelter in young rolled leaves of its host plant (Larsson et al 1997). This behavior may also be due to nutritional demands, since young leaves are tender and usually contain more nutrients and water than mature leaves (Coley 1983;Ohmart et al 1985).…”
Section: Discussionsupporting
confidence: 52%
“…Leaf shelters are known to protect caterpillars from predators (Damman 1987, Ruehlmann et al 1988, Loeffler 1996, to create favorable microclimates (Henson 1958, Larsson et al 1997, and to increase the quality of the leaves on which they feed. (Sagers 1992, Costa & Varanda 2002.…”
Section: Discussionmentioning
confidence: 99%
“…Häggström and Larsson (1995) and Kendall et al (1996) reported wintering in fissures of bark and litter (or in other hidden places). Sage et al (1999) found imagoes in aggregations (as many as 20 individuals) Larsson 1995;Larsson et al 1997). In Great Britain, imagoes colonize host plants for a period of about 2 weeks, viz from the end of March to mid-April (Sage et al 1999) or in April and May (Kendall et al 1996).…”
Section: Hibernation and Leaving Winter Habitatsmentioning
confidence: 99%